Simulation of Multilayer Mirror Design for Visible region Using MATLAB Language - Asmail, Fouad A.; Roomy, Harkat M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, the theoretical study for designing of dielectric mirrors of high reflectance in the visible region of electromagnetic spectrum between wavelength of 400-700 nm is presented, and searching on the performance properties of the design, like there reflectance as a function to the wavelength, as beam incident in a normal form, for the materials of neglected absorbance, and scattering, in the form of thin film deposition, which are deposited on glass substrate, and by using matrix system in the study, which are used as computer simulation in MATLAB code. The materials which are used in this study are represented by ( AlAs ), (TiO2 ),( SiC ), and (Si3N4 ), which used in the designing mirrors alternating on the refractive index in the form of stacks series of quarter wavelength with high and low refractive index to get dielectric mirrors of low losses and high reflectance. From the results, the high difference of refractive index gave high reflectance with lower number of layers